Scientific Parental Studies of FITK Lecturer State Islamic University of North Sumatra Medan - Mardianto Mardianto; Juli Julaiha P; Muhammad Syah Bagus (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Scientific development within UIN North Sumatra Medan must lead to efforts to create Wahdatul Ulum. However, on the other hand, the map of lecturer distribution from recruitment patterns to lecturer transfers and rotations still experiences many obstacles, this is because there is no integrated policy, where authority can be exercised completely by the Faculty of Science, Tarbiyah and Teacher Training, FITK UIN North Sumatra, Medan. This research aims to describe the scientific parental knowledge of lecturers at FITK, North Sumatra State Islamic University, Medan. This type of research uses research and development (RnD). This research concludes that the results of product effectiveness testing in website-based scientific parental application development research are 0.001 ≤ 0.05. This means that these results show that using this media will be more effective and practical to use. This shows that the product resulting from research into the development of website-based scientific parental application media, namely the